Produção de salame tipo italiano através de cura natural com extratos de aipo e acelga - Biasi, Vanessa (2010)
The meat industry is always alert to consumer s requirements. Consumer s are now in search for healthier products, once they are changing their food habits. The sodium nitrite and other chemical preservatives are related to diseases such as cancer and, because of that, food products without the use of cure agents, or naturally cured, are being largely studied. From vegetable extracts and a nitrate reducing starter culture can prepare cured meat products similar to the conventionally cured. The objective of this research was to develop and evaluate the quality of Italian salami produced by natural curing, using celery and Swiss chard extracts as nitrate source, with or without a nitrate reducing starter culture. Six treatments were evaluated (T1 0,8% celery extract and pre-incubated starter culture; T2 0,8% celery extract and no incubated starter culture; T3 1,2% celery extract and pre-incubated starter culture; T4 0,3% celery extract; T5 0,3% celery extract and pre-incubated starter culture; T6 0,3% Swiss chard and pre-incubated starter culture) and a control (sodium nitrate and sodium eritorbate). Physical-chemical analysis (pH, proximate composition, water activity, sodium nitrite and nitrate, color and TBARS (thiobarbituric test)), microbiological analysis (coliforms at 45ºC, Staphylococcus coagulase-positive, Salmonella sp., sulfite-reducing Clostridium and lactic acid bacteria) and sensory evaluation were done during the maturation period at 0, 1, 4, 7, 10, 15 and 32 days. During the storage period, the oxidative activity (TBARS) and the color of the salami, at 30, 60 and 90 days were evaluated. All treatments showed a development of the typical color of cured meat products and the physical-chemical and microbiological results corresponded to the Brazilian official food regulations. In the sensorial analyses, all treatments were considered worst than control, although treatments T4, T5 and T6 were considered acceptable. The attribute considered most different by the testers was the flavor followed by the odor. During the storage period, the color of the treatments was considered similar to the control, but evaluating the a* values, no color stability was observed in the treatments that used lower extract concentrations, and these values were higher in the treatments than the ones used in the pre-incubated starter culture. Meanwhile, for the color development the pre-incubation time was not necessary. At the end of the storage period, the control showed the highest TBARS value, demonstrating that the vegetable extracts used had an anti-oxidation effect.